Behaviour of FRP-confined coal reject concrete columns under axial compression. (15th April 2021) - Zhao, Hongchao; Ren, Ting; Remennikov, Alex
Abstract: The relatively low strength and brittleness are believed to be two main factors restricting the widely use of coal reject concrete (i.e. CRC) in practical applications. This paper presents a concept of the novel hybrid concrete column incorporating fibre-reinforced polymer (i.e. FRP), termed FRP-confined CRC (i.e. FCCR) columns, to widen the use of CRC. The systematic compression tests on natural aggregates concrete (i.e NAC) and CRC with the large range replacement ratios of natural aggregates in volume (i.e. 0%, 25%, 50%, 75% and 100%) were firstly carried out, followed by the compressive tests on FCCR columns. Test variables covered the thickness of FRP jacket (i.e.0-ply, 2-ply and 4-ply), the replacement ratio of natural aggregates and the particle size of coal reject. In parallel, the FRP-confined NAC columns (i.e. FCNA) columns have been prepared and tested for comparison. Test results showed that the compressive strength of CRC decreases with the increased replacement ratio of natural aggregates. When the CRC is confined by the exterior FRP jacket, both the compressive strength and the ductility of which have been significantly enhanced. Furthermore, these FCCR columns with a thicker FRP jacket generally exhibited the superior compressive behaviour. The analysis-oriented model developed by Jiang and Teng for FCNA was adopted to predict the compressive behaviour of FCCR. The feasibility of Jiang and Teng's model for predicting the behaviour of FCCR with the replacement of fine aggregate was verified.